Perioperative cardiac arrest and mortality in trauma patients: A systematic review of observational studies - Braz, Leandro G. [UNESP] (2020)
Study objective: Factors that influence the occurrence of perioperative cardiac arrest (CA) and its outcomes in trauma patients are not well known. The novelty of our study lies in the performance of a systematic review conducted worldwide on the occurrence of perioperative CA and/or mortality in trauma patients. Design: A systematic review was performed to identify observational studies that reported the occurrence of CA and/or mortality due to trauma and CA and/or mortality rates in trauma patients up to 24 h postoperatively. We searched the MEDLINE, EMBASE, LILACS and SciELO databases through January 29, 2020. Setting: Perioperative period. Measurements: The primary outcomes evaluated were data on the epidemiology of perioperative CA and/or mortality in trauma patients. Main results: Nine studies were selected, with the first study being published in 1994 and the most recent being published in 2019. Trauma was an important factor in perioperative CA and mortality, with rates of 168 and 74 per 10,000 anesthetic procedures, respectively. The studies reported a higher proportion of perioperative CA and mortality in trauma patients who were males, young adults and adults, patients with American Society of Anesthesiologists (ASA) physical status ≥ III, patients undergoing general anesthesia, and in abdominal or neurological surgeries. Uncontrolled hemorrhage was the main cause of perioperative CA and mortality after trauma. Survival rates after perioperative CA were low. Conclusions: Trauma is an important factor in perioperative CA and mortality, especially in young adult and adult males and in patients classified as having an ASA physical status ≥ III mainly due to uncontrollable bleeding after blunt and perforating injuries. Trauma is a global public health problem and has a strong impact on perioperative morbidity and mortality.